O ENSINO DE CIÊNCIAS E EDUCAÇÃO AMBIENTAL: a formação de sujeitos ecológicos a partir do Ensino Fundamental. - ALMEIDA, Waldelice Oliveira (2019)
The current educational paradigms, regarding the science teaching, point to the need to promote a teaching focused on citizenship by stimulating the construction of values and attitudes in the subjects in formation, through critical and participatory reflection in society, attacking the knowledge to be acquired in a meaningful way. With regard to the role of educator, it is understood as important to stimulate practices in line with ecological ideals, since in this bias it provides to develop attitudes and behaviors ecologically accepted orienting the choices towards the protection of the environment. Thus, the present dissertation addressed a discussion that concerns the relationship between Science teaching and Environmental Education for the training of ecological subjects from Elementary School. The theoretical references used to guide the discussions were based mainly on Carvalho (2012), Reigotta (2014), Freitag, Motta e Costa (1993), Krasilchik (1987), Mello and Longhini (2013), Maknamara (2009) as well as the National Curricular Parameters (1997), the National Curricular Common Base (2017), the National Environmental Education Policy - Law No. 9,795 / 1999, the State Environmental Education Policy - Law No. 9,279 of October 20, 2010. The study uses the perspective of qualitative research whose data collection was carried out in six schools of the municipal network of. with the subjects of Science teachers with which questionnaires and interviews were applied with the objective to investigate the conceptual, scientific and social education on Environmental Education as well as a brief analysis of didactic materials used by these teachers with the purpose of characterizing the pedagogical actions of an environmental nature l developed by them. The results indicated that the insertion of environmental education in schools still presents difficulties, is conditioned to their presence in textbooks, which organize the content and plan the actions and the ecological subjectivity of the teacher. In agreement with the professional master's degree, the product of this research was configured in a paradidatic that sought to effect the presence of environmental education in a contextualized way, taking into account the local characteristics and the social-environmental perspective.